Gain-of-Function Mutant p53 R273H Interacts with Replicating DNA and PARP1 in Breast Cancer - Xiao, Gu (Cancer Res, 2019)
Over 80% of Triple Negative Breast Cancers (TNBC) express mutant p53 (mtp53) and some contain oncogenic gain-of-function (GOF) p53. We previously reported that GOF mtp53 R273H upregulates the chromatin association of Mini Chromosome Maintenance (MCM) proteins MCM2–7 and Poly-ADP-Ribose Polymerase (PARP) and named this the mtp53-PARP-MCM axis. In this study we dissected the function and association between mtp53 and PARP using a number of different cell lines, patient-derived xenografts, tissue microarrays (TMAs), and The Cancer Genome Atlas (TCGA) database. Endogenous mtp53 R273H and exogenously expressed R273H and R248W bound to nascent EdU-labeled replicating DNA. Increased mtp53 R273H enhanced the association of mtp53 and PARP on replicating DNA. Blocking poly-ADP-ribose gylcohydrolase also enhanced this association. Moreover, mtp53 R273H expression enhanced overall MCM2 levels, promoted cell proliferation, and improved the synergistic cytotoxicity of treatment with the alkylating agent temozolomide in combination with the PARP inhibitor (PARPi) talazoparib. Staining of p53 and PARP1 in breast cancer TMAs and comparison with the TCGA database indicated a higher double-positive signal in basal-like breast cancer than in Luminal A or Luminal B subtypes. Higher PARP1 protein levels and poly-ADP-ribosylated proteins were detected in mtp53 R273H than in wild-type p53-expressing patient-derived xenograft samples. These results indicate that mtp53 R273H and PARP1 interact with replicating DNA and should be considered as dual biomarkers for identifying breast cancers that may respond to combination PARPi treatments.